2022
DOI: 10.9734/ijpss/2022/v34i2331612
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genotypes X Environment Interaction of Black Gram (Vigna mungo (L.) Hepper) Using Multivariate Analysis

Abstract: Twenty black gram genotypes were evaluated at five different locations of middle Gujarat in kharif 2016 to assess the genotype x environmental interactions in RBD design with two replications. The data were analyzed according to the AMMI model and AMMI based stability measures (ASV Wi(AMMI) and ASTABi). Analysis of variance on the data pooled over locations and G x E interaction was found significant indicated genotypes performed differently in different locations. IPCA1 and IPCA2 were found significant in AMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…This demonstrated that the biplot constructed by the first principal component scores of genotypes and environments against the respective scores of the second principal component adequately represented the environment-centered data. These findings were in harmony with the earlier reports by Jeberson et al (2022) and Parmar et al (2022) in blackgram, wherein they also observed 90% of the total GGE variation in the first two principal components.…”
Section: Resultssupporting
confidence: 92%
“…This demonstrated that the biplot constructed by the first principal component scores of genotypes and environments against the respective scores of the second principal component adequately represented the environment-centered data. These findings were in harmony with the earlier reports by Jeberson et al (2022) and Parmar et al (2022) in blackgram, wherein they also observed 90% of the total GGE variation in the first two principal components.…”
Section: Resultssupporting
confidence: 92%